Некоторые свойства функции Ляпунова на множестве состояний - Гурко, А. Г. (НТУ "ХПИ", 2010)
Введено понятие "дна" функции Ляпунова как прямой, которая делит пополам отрезки, заключенные внутри линий равного уровня функции Ляпунова и параллельные вектору коэффициентов, определяющих направление действующих на объект управления внешних воздействий. Доказано существование "дна" функции Ляпунова и найдено его уравнение. Показано, что приращение значения функции Ляпунова при перемещении произвольной точки от "дна" на любое расстояние по прямой, параллельной указанному вектору, постоянно.

The concept of a "bottom" of Lyapunov function is introduced. A "bottom" of Lyapunov function is a straight line, which divided into equal parts the segments of lines placed between the lines of equal level of Lyapunov function and parallel to the vector of coefficientsthat determinethe direction of acting of externalinfluences at the control object. The existence ofthe "bottom" of Lyapunov functionis proved and its equation is obtained. It is shown that the increment of value of Lyapunov function when an arbitrary point transferences along the lines of referred above vector, constantly.
Keywords: объект управления; функция Ляпунова; множество состояний